2018
DOI: 10.4028/www.scientific.net/ssp.277.188
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Strain State of a Flat Tractive-Bearing Element of a Lifting and Transporting Machine at Operational Changes of its Parameters

Abstract: Main indicators of a stress-strain state of a rubber-cable belt, the rubber-cable rope for a random placement pattern and the size of the part with broken cables, including partially removed cables, with cable breakages and their random amount, different conditions of belt interaction in its cross-sections of connection to structural elements of a conveyor and a lifting machine to ensure control of its tractive ability during the life cycle. Performed researches clarify the idea of the interaction mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…RS3 Rocscince software embodying the well-known finite element method (FEM) is used to simulate three-dimensional rock stress-strain state (Kolosov, Bilous, Tantsura, & Onyshchenko, 2018) near the cross-heading face and RS2 (PHASE2) is applied to study the twodimensional stress-strain state in plane cross-sections.…”
Section: Numerical (Fem) Simulation Of the Cross-heading Advancementioning
confidence: 99%
“…RS3 Rocscince software embodying the well-known finite element method (FEM) is used to simulate three-dimensional rock stress-strain state (Kolosov, Bilous, Tantsura, & Onyshchenko, 2018) near the cross-heading face and RS2 (PHASE2) is applied to study the twodimensional stress-strain state in plane cross-sections.…”
Section: Numerical (Fem) Simulation Of the Cross-heading Advancementioning
confidence: 99%
“…Thus, the experience of applying a goaf stowing to the mined-out space indicates that prerequisites can be created for solving a whole complex of engineering and technical problems [39] in addition to reducing the number of rocks emitted from mines and improving due to this the ecological situation in coal-mining regions, the successful implementation of the protection of surface objects and the maintenance-free support of preparatory workings.…”
Section: Substantiation Of Ways To Reduce the Negative Consequences Omentioning
confidence: 99%
“…In [8], it has been revealed that after cryogenic treatment, the static strength of synthetic diamonds increases, caused by an irreversible change in the initial stress-strain state of the crystals, due to the ordering of the crystal lattice defective structure. In [9][10][11] a fl at model of the interaction of elements (cables) in a composite product is presented through a material binding them, which has excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%